1998
DOI: 10.1038/sj.bjc.6690051
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of intratumoral microvessel density, p53 expression and survival in colorectal cancer

Abstract: Summary Adjuvant treatment of patients with colorectal cancer is hampered by a lack of reliable prognostic factors in addition to the clinicopathological staging system. A poorly defined but considerable fraction of Astler-Coller stage B patients will experience tumour recurrence, and some of the stage C patients will probably survive for a prolonged time after surgery without adjuvant treatment. Assessing parameters related to tumour angiogenesis has provided valuable prognostic information in different tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
2
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 39 publications
6
82
2
2
Order By: Relevance
“…Tomisaki et al (1996), in assessing an association correlation between MVD and liver metastasis, found a mean MVD of 64 in colorectal cancer patients with hepatic metastasis compared with a mean MVD of 52 in patients without metastasis (P ¼ 0.001). In addition, the relationship in colorectal cancer between MVD and prognosis has also been described in most studies indicating a positive correlation between high MVD and poor outcome (Vermeulen et al, 1999;Li et al, 2003). We have shown a direct relationship between increasing MVD and cancer-specific survival.…”
Section: Discussionmentioning
confidence: 49%
“…Tomisaki et al (1996), in assessing an association correlation between MVD and liver metastasis, found a mean MVD of 64 in colorectal cancer patients with hepatic metastasis compared with a mean MVD of 52 in patients without metastasis (P ¼ 0.001). In addition, the relationship in colorectal cancer between MVD and prognosis has also been described in most studies indicating a positive correlation between high MVD and poor outcome (Vermeulen et al, 1999;Li et al, 2003). We have shown a direct relationship between increasing MVD and cancer-specific survival.…”
Section: Discussionmentioning
confidence: 49%
“…It has already been demonstrated that neovascularization is associated with tumor growth and that the possibility exists that tumors with greater numbers of microvessels are related to metastases 16,17,18 . In fact, a relationship between the degree of microvessel density and worse prognosis for colorectal cancer has been observed in several studies 4,5,19 , although this has not been confirmed by some other authors 20,21,22 . These differences in results have been attributed in part to limitations in the traditional method for assessing angiogenesis 7,8,23 .…”
Section: Discussionmentioning
confidence: 80%
“…Oxaliplatin, bevacizumab and cetuximab are some of these drugs which have been recently approved and recognized as effective in enhancing the results of chemotherapy for colon cancer. An association between the degree of angiogenesis expression and the prognosis for colorectal adenocarcinoma cases has also been reported 3,4,5 . A recent review on histomorphological aspects of angiogenesis and neoangiogenesis has shown that a judicious combination of microscopic angiogenic parameters should be an integral component of tumor staging system 6 .…”
Section: Introductionmentioning
confidence: 78%
“…VEGF expression in primary CRC seems clearly associated with increased chances of dissemination. Moreover, increased VEGF in the primary tumor has been associated with a poor prognosis as positive tumor expression has been correlated with a twofold increase risk of death and an increased risk of tumor recurrence (Ishigami et al, 1998;Vermeulen et al, 1999).…”
Section: Angiogenesismentioning
confidence: 99%